1991
DOI: 10.3109/00016349109007923
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Cytobrush® and Papaplast® in Sampling Vaginal Smears

Abstract: The ability of Cytobrush and Papaplast to collect endocervical cells in vaginal smears was tested in a prospective randomized comparative study including 107 women. Endocervical cells were found more often and in greater numbers with Cytobrush, also in women over 50 years of age. Papaplast missed endocervical cells twice as often as did Cytobrush. The use of the latter instrument meant that the number of repeat smears necessitated due to the absence of endocervical cells could be considerably reduced, with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

1993
1993
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
3
0
3
Order By: Relevance
“…In current literature there are numerous studies which show that cervical brush is an excellent instrument for carrying out endocervical cytologic sampling (7–10). Thus, it has been demonstrated that the combined use of the brush and the wooden spatula yields better results than when used separately (11–13).…”
Section: Discussionmentioning
confidence: 99%
“…In current literature there are numerous studies which show that cervical brush is an excellent instrument for carrying out endocervical cytologic sampling (7–10). Thus, it has been demonstrated that the combined use of the brush and the wooden spatula yields better results than when used separately (11–13).…”
Section: Discussionmentioning
confidence: 99%
“…O estudo também corroborou os resultados daqueles que comprovaram a superioridade da combinação espátula-escova, quando defrontada com as espátulas modificadas 8,16 . Corroborou ainda os achados daqueles que demonstraram que a espátula de Ayre, utilizada isoladamente, é um método deficiente na produção de esfregaços satisfatórios 11,12 .…”
Section: Discussionunclassified
“…Foram considerados satisfatórios aqueles esfregaços contendo mais de 200 células escamosas, mais de 10 células metaplásicas e mais de 20 células endocervicais colunares 7,13 . O grau de sangramento também foi avaliado e quantificado (nenhum, pouco, moderado e abundante) 8,10 . Esfregaços contendo quantidade excessiva de sangue e/ou material purulento e aqueles com material insuficiente para avaliação foram excluídos da análise 9 .…”
Section: Pacientes E Métodosunclassified
See 1 more Smart Citation
“…Two others randomly assigned use of each sampling device to certain time blocks (34, 45). The most popular and perhaps most economical design was the use of each subject as her own control, used in 14 studies (42%) (28–32, 35–37, 39–41, 52, 53, 55). This involved taking samples with both experimental and control devices from a subject in a single session or, as in two cases, comparison with smears taken from the same subjects the year before.…”
Section: Methodsmentioning
confidence: 99%